Reaction of 1,3,5-tri-tert-butylbenzene with 2,4,6,8-tetraiodo-2,4,6,8-tetraazabicyclo[3.3.0]octane-3,7-dione - Nguen Kh. M.; Chaikovskii V. K. Vitold Kazimirovich; Filimonov V. D. Viktor Dmitrievich; Funk A. A. (2012, 2012)
Title screen